2020
DOI: 10.1080/21623945.2019.1709253
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the role of bitter taste receptor in extra oral tissues: TAS2R38 is expressed in human adipocytes

Abstract: Increasing evidence indicates that taste receptors mediate a variety of functions in extraoral tissues. The present study investigated the expression of bitter taste receptor TAS2R38 in human adipocytes, the possible link with genetic background and the role of TAS2R38 in cell delipidation and lipid accumulation rate in vitro. Subcutaneous (SAT) and visceral (VAT) adipose tissues were collected in 32 obese and 18 lean subjects. The TAS2R38 gene expression and protein content were examined in whole tissues, dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Alternatively, as human skin is composed of various cell types including melanocytes and adipocytes, both keratinocytes and non‐keratinocyte sources may contribute to the observed levels of TAS2R14 expression. Human subcutaneous adipocytes have been shown to express functional TAS2R38 33 …”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, as human skin is composed of various cell types including melanocytes and adipocytes, both keratinocytes and non‐keratinocyte sources may contribute to the observed levels of TAS2R14 expression. Human subcutaneous adipocytes have been shown to express functional TAS2R38 33 …”
Section: Discussionmentioning
confidence: 99%
“…As their name implies, bitter T2Rs respond to notably bitter compounds and these receptors and their activators have been found throughout the body. Notably, bitter chemicals have been shown to alter food intake via modulation of ghrelin ( Janssen et al, 2011 ), contribute to lipid metabolism ( Cancello et al, 2020 ), and accelerate microorganism clearance in the ciliated airway ( Shah et al, 2009 ). With respect to the liver, bile acids are extremely bitter substances ( Sansome et al, 2020 ), leading to speculation that some of the identified T2Rs respond to these steroid acids that are produced by the liver.…”
Section: Discussionmentioning
confidence: 99%
“…However, as a G protein-coupled receptor, the bitter receptor has seven transmembrane α helixes, which showed difficulty in the isolation and purification of bitter receptors. 52 Thus, the OBPs are excellent alternatives for the construction of bitter biosensors. Besides, the limits of detection using the OBP-based biosensor are even lower than those using bitter taste receptor-based biosensors.…”
Section: Discussionmentioning
confidence: 99%